ChemInform Abstract: Challenges and Advances in the Field of Self‐Assembled Membranes. Issue 40 (12th September 2013) - van Rijn, Patrick; Tutus, Murat; Kathrein, Christine; Zhu, Leilei; Wessling, Matthias; Schwaneberg, Ulrich; Boeker, Alexander
Abstract Review: 50 refs.